Effects of shading and solar reflection from surrounding built environment on building performance - Bhagat, Prateek; S, Amalan Sigmund Kaushik (Science, Engineering and Health Studies, 2025)
Awareness regarding the threats posed to individuals and property by uncontrolled solar reflections from the built environment has been increasing. Despite the severe adverse effects of uncontrolled solar reflections, legislation governing them is remarkably limited, and existing standards are not widely accepted. Without a proper methodology, designers cannot accurately evaluate the effect of a projected building’s reflections until after construction. This study developed a methodology to investigate the effects of shading and sunlight reflections from surrounding buildings. A toolchain was developed using the parametric design platform Rhino3D and Grasshopper. An existing scenario involving spatially proximal buildings in Gurugram was identified, modelled, and simulated. Compared with a standalone building simulation, the southwest and northwest façades experienced a 12% and 28.9% increase in total solar radiation, respectively, because of reflections from surrounding buildings. These findings demonstrate that standalone building simulations are not reliable predictors of energy consumption. The novel methodology developed in this study can be used to evaluate the effects of shading and sunlight reflections from the surrounding built environment.